BLIND PEOPLE BEHAVIORS TO THE ARCHITECTURE OF SEKOLAH LUAR BIASA (SLB) MTS YAKETUNIS - Harry, KURNIAWAN; Tiara, MAHARANI Rizka; Rahmawati, Hs Atika (DIMENSI (Journal of Architecture and Built Environment), 2014)
People who are considered as users or even the inhabitants are the central issue in architecture; therefore it is essential to understand them before making the design. One of the users who have special character are blind people. This paper discusses the interaction between architecture and blind people by observing the blind students’ mobility at Sekolah Luar Biasa (SLB)/extraordinary school MTs Yaketunis Yogyakarta. This research also conducted interviews to confirm the observation result. The purpose of the research is to identify the characteristics of blind people during their interaction with architecture and elements of architecture. The observation and interview done during the research has been recorded several interesting facts, such as how they walked through the corridor, the arrangement method of information about rooms, and the way to find each room. This information is expected to be useful information for creating better and more suitable environment for them.